The Grid Iron Patterns & Detached Villas as the Main Drivers of Sharjah City’s Urban Sprawl - MOHAMED, SHAMSELDIN SAEED (2021)
The city of Sharjah is among the Gulf cities that have increased in size at an unprecedented rate by all standards, and within a period of time not exceeding four decades, after it remained confined within its old wall since its inception until the beginning of the seventies of the last century, with an area of 2.5 square kilometers. This is due to the tremendous political, economic and demographic transformations that are affecting the region in general and the city of Sharjah in particular. On the demographic side, the massive external population migration that trickled towards the city resulted in a major defect in its demographic structure, which represented a decrease in the percentage of the citizen population to only about 10% of the non-citizen population. On the other hand, in contrast to this phenomenon, the percentage of citizens' housing areas amounted to about 90% of the total area of the administrative boundaries of the city, as the city expanded at an accelerated rate and consumed vast areas of its urban land stock which is now almost exhausted, as indicated by the outputs of the city's housing plan. This rapid growth coincided with two phenomena worthy of attention, the first being the conjunction of this growth with the significant decline in residential density, and the second with the phenomenon of the increase in the proportion of non-durable residential lands, which reached 49% (DTPS, 1998) of the total land allocated to citizens. Among the most prominent consequences of the last phenomenon: - 1. Reconstructed plots of land are scattered between residential extension areas equipped with infrastructure services and roads, indicating the weak economic efficiency of these high-cost services as an inevitable consequence of the low density. 2. The city fulfills the conditions for defining the phenomenon of irregular urban sprawl and the negative consequences thereof. 3. The lack of adherence to the principles of sustainable development with regard to the efficiency of urban land management to meet the current housing demand and without prejudice to the rights of future generations in housing services. This research aims to explore and monitor the basic reasons behind the phenomenon of accelerated urban sprawl that the city is witnessing, and that is based on answering some logical questions such as: 1. How was the ancient nucleus of the city able to accommodate the city's residents and its activities within its old wall, with an area not exceeding 2.5 square kilometers, from its first inception until the beginning of the seventies of the last century? 2. Why did the citizens' housing areas expand at these standard rates after surpassing the old core? The analytical study proved that the organic pattern of the urban fabric of the city and the traditional housing model with an inner courtyard, which have met, throughout history, the climatic, social and religious requirements are the reason behind the assimilation of the ancient core of the city to its residents and activities throughout the mentioned period. On the other hand, the same study proved that the grid system and the villa model are the main reason behind the urban sprawl of the city. The research chapters include a detailed study of all the mentioned elements and some recommendations and proposals related to mitigating the negative consequences of the unprecedented urban sprawl of the city.